2017
DOI: 10.1111/avsc.12298
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and impoverishment of fen communities in a eutrophicated agricultural landscape of the Czech Republic

Abstract: Abbreviations EUNIS = European Nature Information System; PERMDISP = Test of homogeneity of dispersion; RMANOVA = Analysis of variance for dependent samples; RMSEP = Root meansquared error of prediction. Nomenclature Ku cera et al. (2012) for bryophytes; Danihelka et al. (2012) for vascular plants; Chytr y (2012) for plant communities AbstractQuestions: On-going rapid loss of fen biodiversity in Central Europe is well known, but rigorous testing of this is complicated. We compared historical and present-day ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…Plant diversity of fen peatlands can vary significantly and be influenced by a myriad of factors, including soil fertility (Øien et al 2018), soil water level and chemistry (Navrátilová et al 2017) and changes to hydrological conditions like drainage and rewetting (Mälson et al 2008). Vegetation management practices like mowing (Kozub et al 2019) and grazing (Merriam et al 2018) can also affect fen plant diversity, since the abandonment of fens may result in changes to vegetation composition (Navrátilová et al 2017) and the encroachment of shrubs over herb fens (Wheeler and Shaw 1995). Regular mowing and grazing and the maintenance of water and nutrient levels can have positive effects on the long-term survival of characteristic open fen vegetation (Stammel et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Plant diversity of fen peatlands can vary significantly and be influenced by a myriad of factors, including soil fertility (Øien et al 2018), soil water level and chemistry (Navrátilová et al 2017) and changes to hydrological conditions like drainage and rewetting (Mälson et al 2008). Vegetation management practices like mowing (Kozub et al 2019) and grazing (Merriam et al 2018) can also affect fen plant diversity, since the abandonment of fens may result in changes to vegetation composition (Navrátilová et al 2017) and the encroachment of shrubs over herb fens (Wheeler and Shaw 1995). Regular mowing and grazing and the maintenance of water and nutrient levels can have positive effects on the long-term survival of characteristic open fen vegetation (Stammel et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to our expectations, fencing reduced the frequency of peat‐forming species, and increased the frequency of upland and facultative upland species. Some authors have found that in the absence of mowing or grazing, species composition can shift to reflect the underlying hydrology (Fojt & Harding, ) or nutrient status (Navrátilová, Hájek, Navrátil, Hájková, & Frazier, ) of the fen. Although species composition in fens is primarily determined by the depth of the water table, pH and nutrient availability, livestock grazing can modify species composition by influencing species competitive interactions and tolerances to soil moisture and nutrient status (Fossati & Pautou, ; Schrautzer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Navrátilová et al. () concluded that eutrophication and lack of management has resulted in near extinction of nutrient‐poor, alkaline fens (i.e. rich fens) and their associated species across Central Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Navrátilová et al. ; Schweiger & Beierkuhnlein ), four in forests (Becker et al. ; Heinrichs & Schmidt ; Reczyńska & Świerkosz ; Vild et al.…”
Section: The Applied Vegetation Science Special Featureunclassified